POLLEN OF INVASIVE PLANT SPECIES IN HONEY FROM BOSNIA AND HERZEGOVINA - Bakić, Velida; Muratović, Edina; Trakić, Sabina; Đug, Samir (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Invasive species represent a serious ecological problem of today, and due to the modest needs for environmental conditions and the abundant production of nectar and pollen, they are an important factor endangering the indigenous honey flora. Given that there are 100 honey plants in Europe that are the basis for the production of monofloral species of honey, it is of special interest to preserve the diversity of the indigenous apiflora of Bosnia and Herzegovina.For the purposes of this research, 100 melissopalynological profiles of honey from different botanical and ecological regions were analyzed. The analysis of palynological profiles of the collected samples determined the presence and based on micromorphological elements, invasive species were identified in the honey we consume.